Make Eating Out a Healthier Experience - Shari Bresin; Lori Johnson; Anghela Z. Paredes; Karla P. Shelnutt (EDIS)
This publication discusses ways to make healthier choices when dining out. Written by Shari Bresin, Lori Johnson, Anghela Z. Paredes, and Karla P. Shelnutt, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised October 2023.